Diagnostic accuracy of squash cytology in central nervous system tumors - Shrestha, Ram Kumar; KC, Bibek; Sedain, Gopal; Sayami, Gita; Shilpakar, Sushil; Sharma, Mohan Raj; Pradhanang, Amit Bahadur; Kafle, Prakash; Rajbhandari, Binod (Journal of Society of Surgeons of Nepal, 2017)
Introduction: CNS tumor requires intraoperative decision making regarding the extent of tumor removal. Clinical examination and imaging studies are not sufficient enough to predict the biological behavior of the tumors. Squash cytology is a quick method of evaluation of cytomorphologic features prepared from smear technique and provide the preliminary diagnosis and aid in intraoperative decision making by differentiating neoplastic from non neoplastic and benign from malignant lesions. The aim of this study is compare the diagnostic accuracy of squash cytology to that of histopathological examination. Methods: This study consists of 36 specimens from both brain and spine subjected to both squash cytology and histopathological evaluation. The squash preparation and histopathological finding were later compared and diagnostic accuracy calculated. Results: Gliomas are the most common tumor encountered and the accuracy of Squash cytology obtained was 71%. In meningioma, 100% diagnostic accuracy was obtained however, there was limitation in accurately predict the subgroup of tumor by squash cytology alone. Other neoplastic lesions included in this study were Schwannoma, Oligodendroglioma, Ependymoma, mixed tumors and others. Overall, the accuracy predicted by squash cytology is found to be 77.8 % in this study. Conclusion: Squash cytology is rapid and reliable method of tissue diagnosis that aid in intraoperative decision making regarding the extent of Central Nervous System tumor excision